Perceptual Experiences of (Depicted) Absence - Voltolini, Alberto (JoLMA, 2024)
At least since Sorensen (2008) and Farennikova (2013), an important debate has been raised as regards whether one can experientially perceive absences. Three main positions have been discussed: radical perceptualism, cognitivism, and metacognitivism. In this paper, first of all, I want to claim that perceptualism can be maintained in a moderate form, once one explains the proper role that the relevant expectations play, as weakly cognitively penetrating one’s perception of absence in its phenomenal difference from a previous perceptual experience. Moreover, I want to claim that a similar result can be applied to pictorial perceptual experiences of absences, once one takes pictorial experience as a genuine yet sui generis perceptual seeing-in experience.